Diseño e implementación de alumbrado con bombillas tipo Led bajo los requisitos exigidos por RETILAP en la Casa Máquinas – Unidades Principales – Estación Vasconia- Cenit, Puerto Boyacá (2023)
This project is carried out with the design and execution of an improvement proposal with LED lighting in the area of the Vasconia station machine house, Cenit - Puerto Boyacá, in order to guarantee adequate illuminance levels for a work environment. safe and efficient, taking into account the technical lighting regulations (RETILAP).